Geological and economic criteria on the existence of scandium in the lateritic deposits of Moa, Cuba - Alain Carballo-Peña; José Nicolás Muñoz-Gómez; Gerardo Antonio Orozco-Melgar; Arturo Luis Rojas-Purón (Minería y Geología, 2018)
ICP-MS analyses have revealed the existence of scandium in the lateritic nickel and cobalt ores of the Moa region (Cuba). This article reviews the available information about this element and geological and economic criteria are offered about the contents of scandium in the ores of Camarioca East, Yagrumaje North and Yagrumaje South lateritic deposits and in the tailings of the metallurgical plants of the region. The distribution of scandium mineralization in the lateritic profile predominates in the limonitic horizon, where goethite, gibbsite and hematite appear. The reported values of the average contents of scandium show economic potential for developing geological exploration projects that consider the extraction of metal as a byproduct of nickel and cobalt production in Moa, using acid leaching technology under pressure.